Two years after molecular diagnosis of familial hypercholesterolemia: majority on cholesterol-lowering treatment but a minority reaches treatment goal. - Roeland Huijgen (Public Library of Science (PLoS), 2010)
Background The risk of premature cardiovascular disease in patients with familial hypercholesterolemia (FH) can be profoundly reduced by cholesterol-lowering therapy, and current guidelines for FH advocate ambitious low-density lipoprotein cholesterol (LDL-C) goals. In the present study, we determined whether these goals are reflected in current clinical practice once FH has been diagnosed. Methodology/principal findings In 2008, we sent questionnaires to all subjects (aged 18-65 years) who were molecularly diagnosed with FH in the year 2006 through the screening program in The Netherlands. Of these 1062 subjects, 781 completed the questionnaire (46% males; mean age: 42+/-12 years; mean LDL-C at molecular diagnosis (baseline): 4.1+/-1.3 mmol/L). The number of persons that used cholesterol-lowering therapy increased from 397 (51%) at baseline to 636 (81%) after diagnosis. Mean treated LDL-C levels decreased significantly to 3.2+/-1.1 mmol/L two years after diagnosis. Only 22% achieved the LDL-C target level of < or = 2.5 mmol/L. Conclusions/significance The proportion of patients using cholesterol-lowering medication was significantly increased after FH diagnosis through genetic cascade screening. The attained LDL-C levels were lower than those reported in previous surveys on medication use in FH, which could reflect the effect of more stringent lipid target levels. However, only a minority of the medication users reached the LDL-C target.